Time-varying liquidity in hedge fund returns. - Li, S; Patton, A (Oxford-Man Institute of Quantitative Finance, 2007)
We propose a method for determining the factors that affect the (unobservable) liquidity of hedge fund investments. Our method exploits the link between illiquidity and serial correlation in hedge fund returns established by Getmansky, Lo and Makarov (2004), and does not require information on the actual positions taken by the hedge fund, nor even the 'style' of the hedge fund; we use only the returns reported by the hedge fund and other easily observed information. Using a panel of monthly returns on over 600 individual hedge funds, we find significant evidence of time variation in the degree of liquidity of hedge fund investments. Broadly stated, hedge funds in equity-based styles, such as equity market neutral and equity hedge or non-hedge, exhibit decreases in liquidity when stock market returns are low and bond market returns are high. In contrast, hedge funds in fixed income styles, such as convertible arbitrage or fixed income, exhibit lower liquidity when equity market volatility is high, and when the fund experiences in-flows or out-flows of funds.